The Application of Islamic Boarding School Curriculum Management in Shaping the Independent Character of Students at Darul Atqiya Islamic Boarding School - Murtaki, Kiki (Departement of PAI, Universitas Majalengka, 2025)
Education is very important for the formation and development of independent character. This research examines how students at the Darul Atqiya Majalengka Islamic Boarding School develop their independence through the use of Islamic boarding school curriculum management. This research uses a qualitative approach with a descriptive type through interviews, observation and documentation. The research results show that: Firstly, Islamic boarding school curriculum management in forming the independent character of students is using planning, organizing and evaluating. Secondly, the formation of independent character at the Darul Atqiya Majalengka Islamic Boarding School is more about coaching, namely through exemplary coaching, coaching with advice or encouragement. Third, supporting factors in forming student independence, namely team cohesion, teacher involvement in forming independent character, and student motivation in training or activities. The inhibiting factors are the lack of facilities and infrastructure in Islamic boarding schools, financing factors, and the behavior of students who sometimes lack discipline.